Peran Guru dalam Keberhasilan Penerapan Merdeka Belajar di Sekolah Dasar: Tinjauan dalam Konsepsi Ki Hadjar Dewantara - Lia Hardiani; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The goal of education is to develop the potential of students who can later become democratic and responsible citizens. In developing the potential of students, teachers require flexibility in terms of learning development, teachers need to adapt the learning carried out to the characteristics of students in order to facilitate the potential of each student. The Independent Curriculum provides freedom for schools to innovate, in line with Ki Hadjar Dewantara's idea of education that liberates the body and soul. This study aims to analyze the role of teachers in the successful implementation of the Independent Curriculum based on Ki Hadjar Dewantara's concept. The study uses a descriptive qualitative method through literature study with the steps of selecting, searching, reading, recording, and presenting library sources. In addition, the role of teachers who reflect the Trilogy of Ki Hadjar Dewantara, namely Ing Ngarso Sung Tulodo, Ing Madya Mangun Karso and Tut Wuru Handayani also determine the success of the implementation of the independent curriculum. The end result is that, besides being the spearhead of education, educators must teach and educate students like parents who provide examples, build intentions, and motivate students so that the learning created prepares students to become cultured, character-based, creative, and adaptable individuals. Future research is expected to be able to conduct research using different methods to strengthen the results of previous research.